Poetic start of György Somlyó - Szemes, Péter (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2020)
It was evident for György Somlyó to become a poet, as he was predestinated for that because of his father’s legacy besides his talent. Nevertheless, there was no direct route to success, several pitfalls made his start difficult from an extreme right-wing attack to the rejection of the editor-in-chief of the Nyugat. The study focuses on the first period of the exceptional poet’s poetic career from the inspiring Attila József meeting to Ferenc Baráth’s stimulating criticism: „in the future you will be obliged to cast aside the sea of reminiscence, and stand on your own feet without crutches, on your own intellectual ground!” (Baráth 1939)
Keywords: György Somlyó; Nyugat